Influence of annealing on the optical properties, structure, photosensitivity and chemical stability of As30S70 spin-coated thin films - Šlang, Stanislav; Pálka, Karel; Jain, H.; Vlček, Miroslav (Elsevier Science BV, 2017)
Chalcogenide glass (ChG) thin films prepared by solution based deposition technique offer important advantages over vacuum deposited films, which are useful for many applications especially in infrared optics. Their fabrication, which comprises dissolving the ChG in volatile organic solvent and then depositing thin film by spin coating the solution, is simpler and significantly cheaper. However, contaminants from the solvent are incorporated. The residual organic content in the films is significantly reduced by appropriate thermal treatment. This work reports the influence of specific annealing conditions and UV light exposure on the structure, opto-physical and chemical properties of As30S70 spin-coated ChG films. The results show increase in refractive index with increasing annealing temperature, whereas the thickness and optical bandgap decrease. The UV exposed regions of the samples exhibit positive etching in amine based solvents. The HS-LEIS spectroscopy is used to determine the elemental concentration profile of annealed thin film, which shows almost stable As/S ratio with composition close to that of the source bulk glass. Thus UV light induced structural changes and the mechanism of selective etching are proposed.
Vliv temperace na optické vlastnosti, strukturu, fotocitlivost a chemickou stabilitu tenkých vrstev As30S70 připravených spin-coatingem
Keywords: Chalcogenide glasses; Spin-coating; Thermal treatment; Photo-induced changes; Wet-etching; HS-LEIS; Chalkogenidová skla; Spin-coating; Temperace; Fotoindukové změny; Mokré leptání; HS-LEIS